Low temperature atomic-scale observations of slip traces in niobium. (1st July 2020) - Douat, B.; Bonneville, J.; Drouet, M.; Vernisse, L.; Coupeau, C.
Abstract: Slip traces in body-centred cubic single crystals usually correspond to various slip planes and even, in the case of wavy slip traces, to none identifiable crystallographic slip planes. We recently developed an experimental scanning tunnelling microscope that allows characterizing slip traces at the atomic scale. Unique experimental results obtained at 200 K and 293 K have already been published. We report here new relevant experimental results obtained at 90 K on niobium single crystals, that provide additional information in the understanding of the motion of screw dislocations in bcc metals. Graphical abstract: Image, graphical abstract